Exploration of Factor Analysis Through an Inventory of Psychological Skills for West Sumatra Pencak Silat Athletes - Teressa, Fadillah; Nelson, Sonya; Septri, Septri; Gemaini, Andri (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Study Purpose:The problem in this study is that the psychological skills of West Sumatra martial arts athletes are not yet known. The purpose of this study was to explore the psychological skills of martial arts athletes. Exploring means identifying and analyzing various psychological factors more deeply that affect the performance of martial arts athletes. Methods:This type of research is descriptive quantitative using survey methods and data collection techniques in this study are questionnaires. The population in this study was approximately 300 athletes. This sampling technique uses purposive sampling technique with the criteria of athletes who have participated in national championships. So that the sample in this study amounted to 30 martial arts athletes. Consisting of 15 men and 15 women. The data in this study were analyzed with descriptive statistical analysis. Result. The results showed that motivation (30.8) and mental preparation (24.7) were in the high category, indicating that athletes had a strong drive to train and were well prepared for the competition. However, anxiety control was still in the low category (19.8), which indicated that many athletes had difficulty in managing the pressure of competition. Self-confidence (25.7), attention to the team (20.1) and concentration (20.4) were in the medium category, indicating the need for improvement in these aspects for athletes to achieve more optimal performance.